Dynamics of Variation in Physical Capacity of Elderly People - Lina Kreivėnaitė; Vytautas Streckis; Kristina Visagurskienė; Alfonsas Buliuolis; Asta Lileikienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Increase in physical capacity and ftness can lead to additional improvements in health status, which is so important for healthy aging. Most scientists emphasize the physical activity decline in people of all ages. Therefore, it is important to assess health-related physical capacity and encourage people of various ages to improve their health, physical ftness and the quality of their life. Hypothesis - a signifcant decline in physical capacity of the elderly will be identifed during the research period. Research aim - to identify the variation dynamics of physical capacity indices of elderly people. Research methods. 60-69-year-old males and females were selected for the data analysis (n = 244). The anthropometric data and the physical capacity test results of trunk ﬂexion, sit ups, balance and 1000 meter run were analysed. Physical capacity tests were carried out on the basis of the 'Euroft' test methodology. The methods of descriptive statistics were used for the data analysis. Research results. Body balance (43.8%) and aerobic capacity (20.8%) of the elderly males signifcantly declined (p < 0.05) during the experimental period. However, improvement in the ﬂexibility of males 16.5% (p < 0.05) was identifed. The capacity of trunk ﬂexor muscles of elderly females improved signifcantly by 39.3%, while the balance - by 18.1% (p < 0.05). Analysis of the results in reference to gender showed that the balance, the capacity of trunk ﬂexor muscles and aerobic capacity of elderly females increased signifcantly in comparison with males (p < 0.05). Nevertheless, the ﬂexibility variation of males was higher than the one of females (p < 0.05) at the end of the research period. Discussion and conclusions. The balance and aerobic capacity of elderly males signifcantly decreased, whereas the ﬂexibility improved. The capacity of trunk ﬂexor muscles and balance of elderly females resulted in a statistically signifcant increase. In reference to the gender aspect it was determined that the majority of physical capacity results of elderly females statistically signifcantly developed more than the physical capacity results of males. Keywords: physical capacity, elderly people, 'Euroft'.